Assessment of patient-reported outcomes after polytrauma: protocol for a systematic review. Issue 3 (16th March 2018) - Gnass, Irmela; Ritschel, Michaela; Andrich, Silke; Kuske, Silke; Moschinski, Kai; Herrmann-Frank, Annegret; Metzendorf, Maria-Inti; Flohé, Sascha; Sturm, Johannes; Windolf, Joachim; Icks, Andrea
Abstract : Introduction: Survivors of polytrauma experience long-term and short-term burden that influences their lives. The patients' view of relevant short-term and long-term outcomes should be captured in instruments that measure quality of life and other patient-reported outcomes (PROs) after a polytrauma. The aim of this systematic review is to (1) collect instruments that assess PROs (quality of life, social participation and activities of daily living) during follow-up after polytrauma, (2) describe the instruments' application (eg, duration of period of follow-up) and (3) investigate other relevant PROs that are also assessed in the included studies (pain, depression, anxiety and cognitive function). Methods and analysis: The systematic review protocol is developed in line with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols statement. MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Cochrane Central Register of Controlled Trials and the trials registers ClinicalTrials.gov and WHO International Clinical Trials Registry Platform will be searched. Keywords, for example, 'polytrauma', 'multiple trauma', 'quality of life', 'activities of daily living' or 'pain' will be used. Publications published between January 2005 and the most recent date (currently: August 2016) will be included. In order to present the latest possible results, an update of the search is conducted before publication. The data extraction and a content analysis will be carried out systematically. A critical appraisal will be performed. Ethics and dissemination: Formal ethical approval is not required as primary data will not be collected. The results will be published in a peer-reviewed publication. PROSPERO registration number: CRD42017060825 .